Política moderna - dir. Rui Calafate (Quarto Poder - Sociedade de Comunicação)
Existências: A. 1, nº1 (out. 1998) - A. 1, nº2 (nov. 1998); A. 2, nº17 (fev. 2000) - A. 3, nº32 (mai. 2001); A. 3, nº34 (Ago. 2001).